The Effect of Everyone Is a Teacher Here Learning Model on Science Learning Outcomes of SD Negeri 1 Bukit Tempurung Students - Mirzayani, Reni (Journal of General Education Science, 2022)
This study aims to determine how the influence of the Everyone Is A Teacher Here model on the Science Learning Outcomes of SD Negeri 1 Bukit Tempurung students in the 2021-2022 academic year. The population in this research isis a student of SD Negeri 1 Bukit Tempurung. The sample in this study was taken from a population of 20 students from 1 class, namely class 5A and class 5B, namely 10 female students and 10 male students.The method used is an experimental method which is part of quantitative research. The research design used a quasi-experimental design. Quasi-experimental is a research using two groups, namely the experimental group and the control group. The results showed thatthe application of the Everyone Is A Teacher Here learning model has an effect on learning outcomes and has a good impact on students' attitudes and activities in the classroom. This is shown before using the Everyone Is A Teacher Here learning model, the learning outcomes are low, and after using the Everyone Is A Teacher Here learning model, the learning outcomes are high. Therefore the research hypothesis is accepted for the science learning outcomes of fifth grade students at SDN 1 Bukit Tempurung after obtaining tcount = 6.9 and ttable = 2.09, then tcount > ttable (6.9 . 2.09), which means the null hypothesis (H0)) is rejected and the alternative hypothesis ( H1) is accepted.